Salter-Harris type II fracture of the middle phalanx with concomitant central slip injury in an 11 year old: a case report - Higginbotham, Devan O.; Tsai, Andrew G. (International Journal of Research in Orthopaedics, 2020)
An 11-year-old male sustained an irreducible, completely displaced epiphyseal fracture of the proximal interphalangeal joint (PIPJ) of the middle finger with an associated central slip injury. Central slip injuries occurring in conjunction with Salter-Harris type II middle phalanx fracture are rare entities, with no previously documented case. Our patient underwent open reduction, internal fixation through crossed-pins to achieve reduction and fixation. He was then splinted in extension for six weeks to allow healing of the central slip injury. At 1-year follow-up, the patient had full range-of-motion with no clinical indication of physeal disruption or growth arrest of the repaired digit. We demonstrate a case in which ephiphyseal fractures of the proximal interphalangeal joint with a concomitant central slip injury can safely be treated with open reduction internal fixation combined with a period of immobilization. We characterize a surgical method of reduction and fixation with splinted immobilization and describe lessons learned from this previously unreported case.